Peningkatan Keterampilan Membaca Siswa RA Sunan Ampel Melalui Pelatihan Pembuatan dan Penggunaan Kalender Abjad - Huda, Moch. Faizul; Briliansah, Tri Zanis; Millah, Zukratul; Choir, Miftachul; Rahmawati, Anisa Dwi (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT Early Childhood Education (PAUD) is a level of education carried out before the basic education level which is an effort to develop children aged 0-6 years. Early childhood education is a form of education that focuses on laying the foundation for growth and development. Based on the results of analysis and observations, the Community Service team from KH University. A. Wahab Hasbullah holds seminars or training on making alphabet calendars to help teachers provide an overview of innovative learning methods. The results obtained from reading skills training using the Alphabet Calendar showed that partners' knowledge about recognizing alphabet letters and making learning media increased after the training. This training indirectly has an impact on the Economic, Social, Health and Education sectors. If this alphabetic calendar is made widely in educational institutions, this training will indirectly improve students' reading skills and reduce environmental pollution caused by waste such as used cardboard. Keywords: Training, Innovation, Alphabetical Calendar, PAUD.